2016
DOI: 10.1111/cgf.12885
|View full text |Cite
|
Sign up to set email alerts
|

Space‐Time Bifurcation Lines for Extraction of 2D Lagrangian Coherent Structures

Abstract: We present a novel and efficient technique to extract Lagrangian coherent structures in two-dimensional time-dependent vector fields. We show that this can be achieved by employing bifurcation line extraction in the space-time representation of the vector field, and generating space-time bifurcation manifolds therefrom. To show the utility and applicability of our approach, we provide an evaluation of existing extraction techniques for Lagrangian coherent structures, and compare them to our approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…These directions yield linear approximations of the corresponding LCS and are obtained as the columns of T ( t ) −1 . Previous work [USE13, MBES16] used the real eigenvectors of the Jacobian as an estimate, which, due to their instantaneous nature, are in general not well aligned with the manifolds (Figure 4). In general, DHTs only exist over finite time intervals, which are typically shorter than the time domain.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These directions yield linear approximations of the corresponding LCS and are obtained as the columns of T ( t ) −1 . Previous work [USE13, MBES16] used the real eigenvectors of the Jacobian as an estimate, which, due to their instantaneous nature, are in general not well aligned with the manifolds (Figure 4). In general, DHTs only exist over finite time intervals, which are typically shorter than the time domain.…”
Section: Methodsmentioning
confidence: 99%
“…They define a time‐dependent vector field topology in terms of the steady vector field topology in the steady frame of reference. Closely related to this strictly local approach is that of Machado et al [MBES16]. These authors extract bifurcation lines using the parallel vectors operator from the space‐time domain, which is equivalent to tracking critical points in the Galilean‐invariant frame of reference defined by the feature flow field.…”
Section: Related Workmentioning
confidence: 99%
“…[MSE13] used the PV operator to extract bifurcation lines in 3D steady vector fields, and applied their method to the space-time domain of 2D flows for extracting hyperbolic trajectories [MBES16].…”
Section: Related Workmentioning
confidence: 99%
“…The derivative of the tensor field ∇T is a third-order tensor, for which the definition of eigenvalues and eigenvectors is non-trivial [ZPM07]. This means that we also find structures similar to hyperbolic trajectories in vector fields [MSE13,MBES16]. Further research is necessary in order to be able to distinguish these different features.…”
Section: Performance and Parameter Studymentioning
confidence: 99%
“…Locations where the flow is parallel to an eigenvector of a Jacobian with three real eigenvalues also form stable lines. These hyperbolic trajectories are the centers of simultaneous converging and diverging behavior of the vector field and can be used to extract Lagrangian coherent structures [MSE13,MBES16]. Roth and Peikert [RP98] showed that vortex core lines can equivalently be described as locations where the curvature of streamlines locally vanishes.…”
Section: Introductionmentioning
confidence: 99%